Salinity tolerance study details with means and variances of parameters compiled in a systematic review and meta-analysis - Podbielski, Imke Anna; Schmittmann, Lara; Sanders, Trystan; Melzner, Frank (In: Podbielski, IA et al. (2023): Systematic review and meta-analysis investigating osmolyte concentrations of marine osmoconformers under low salinity stress [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958457, 2023)
All studies included in the meta-analysis are listed with study details such as experimental design, species studied, number of replicates, salinity levels and mean values and variances of the studied parameters. Data are only reported if full data (replication, mean, variation) were given.
Keywords: cellular volume regulation; marine invertebrates; meta-analysis; osmoconformer; osmolytes; osmoregulation; Osmotic stress; salinity tolerance; systematic review